THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN TEACHING WRITING DESCRIPTIVE TEXT: A DESCRIPTIVE QUALITATIVE STUDY OF TENTH GRADE STUDENTS AT ONE OF SENIOR HIGH SCHOOLS IN BANDUNG - Kaltyana, Karista (2017)
This study was aimed to analyze the implementation of project-based learning in teaching writing descriptive texts and to find out students' responses to the implementation of project-based learning in teaching writing descriptive texts. Thirty four students of tenth grade in one of senior high schools in Bandung were participated in this study. This study employed a descriptive qualitative method. The data were obtained through three instruments: observation, students' writings, and questionnaire. The findings revealed that the implementation of project-based learning could help students in writing descriptive text by following the five stages of project-based learning proposed by Patton (2012). Those stages were 1) getting an idea, 2) designing the project, 3) tuning the project, 4) doing the project, and 5) exhibiting the project. Moreover, based on the results of questionnaire, students' responses to the implementation of project-based learning in teaching writing descriptive text showed positive results. The total numbers of 68% (23 of 34) students agreed that the implementation of project-based learning helped them in writing descriptive text. In the end, regarding to the findings and discussions, implementing project-based learning is recommended to be applied in teaching writing descriptive texts.